Web presence analysis of intellectual outputs on the institutional repository of University of Ibadan, Nigeria (2018)
This paper examines the web presence of intellectual outputs (IOs) of lecturers at the University of Ibadan. Some of the lecturers' outputs between the years 2000 and 2014 that were submitted for input into the Institutional Repository (IR) were examined. IOs are scattered around without a central platform to showcase them as institutional collections. Sample survey research design was used for the study. The study found that some of the IOs were not visible on any digital platform prior to the establishment of the University of Ibadan Institutional Repository (UIIR).'This could be due to print published journals and conference proceedings that do not hove World Wide Web (WWW) presence. The paper recommends that IR should be established in all universities in Nigeria to increase the web presence of lecturers' IOs. There should be sensitisation to promote the IOs addition into the IR.